Combined depth-resolved cathodoluminescence spectroscopy and transmission electron microscopy on Al(Ga)N multi quantum well structures. (22nd January 2021) - Hocker, Matthias; Thonke, Klaus; Li, Yueliang; Biskupek, Johannes; Kaiser, Ute; Scholz, Jan-Patrick; Hubáček, Tomáš; Rettig, Oliver; Scholz, Ferdinand
Abstract: A stack of five Al(Ga)N-based quantum wells is investigated by combined laterally and depth resolved cathodoluminescence (CL) spectroscopy in order to distinguish lateral and vertical inhomogeneities of these wells. Transmission electron microscopy (TEM) micrographs provide data for the real sample structure, which enters into the Monte-Carlo simulation of the depth-resolved CL measurements to refine the depth resolution. The comparison of these CL measurements to the results of electron energy loss spectra (EELS) allows to identify local thickness variations of the lower three quantum wells to be the origin of two different luminescence contributions to the overall spectrum. The differentiation of the two groups of quantum wells by depth-resolved CL is demonstrated.